2018
DOI: 10.1038/s41598-018-32717-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of H. pylori eradication on epigenetic alterations related to gastric carcinogenesis

Abstract: The risk of gastric cancer (GC) remains in precancerous conditions, including atrophic mucosa and intestinal mucosa (IM), even after H. pylori treatment. To define the molecular changes following H. pylori eradication, molecular alterations in the gastric mucosa with and without GC were evaluated in a long-term follow-up study. A total of 232 biopsy specimens from 78 consecutive patients, including atrophic gastritis patients with follow-up ≥3 y after successful H. pylori eradication (AG group), patients who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 62 publications
6
50
0
Order By: Relevance
“…In eradication was associated with a significant reduction of miR-124a-3 methylation in both groups, which was consistent with our previous study [34]. In addition, miR-34c independent predictor of metachronous GC risk [37].…”
Section: Cohortsupporting
confidence: 92%
See 4 more Smart Citations
“…In eradication was associated with a significant reduction of miR-124a-3 methylation in both groups, which was consistent with our previous study [34]. In addition, miR-34c independent predictor of metachronous GC risk [37].…”
Section: Cohortsupporting
confidence: 92%
“…In the present study, the methylation of tumor-suppressor miRNAs was identified more frequently in IM and very infrequently in AM. It thus appears that the methylation of these genes is a molecular event that occurs specifically in IM, and also that IM might exhibit a more aggressive state than AM with regard to molecular alterations, as shown in our previous reports [33,34]. Intriguingly, only in H. pylori-eradicated patients, the number of IM samples obtained from three parts of the stomach was significantly higher in patients with GC (the Hp-/GC and Hp-/LDA/GC groups) than in those without GC (the Hp-/AG and Hp-/LDA/AG groups).…”
Section: Cohortsupporting
confidence: 61%
See 3 more Smart Citations